Inkonsistensi Penetapan Status Darurat Banjir Sumatera Bencana Konstitusional: Uji Indikator Status Darurat - Muksalmina; Yustisi, Nabhani; Tasyukur; Joelman Subaidi; Hamdani (Universitas Islam Tribakti Lirboyo Kediri, 2025)
The hydrometeorological floods that struck several regions of Sumatra in late 2025 generated extensive humanitarian impacts, marked by significant loss of life, severe damage to vital infrastructure, and serious disruptions to socio-economic resilience across multiple provinces. Despite the escalation of these impacts, the government did not declare a national disaster emergency status, citing the adequacy of state capacity. This article examines the conformity of this policy decision with the statutory indicators for declaring a disaster emergency as stipulated in Law Number 24 of 2007 and Government Regulation Number 21 of 2008, and analyzes its constitutional implications for the protection of citizens’ fundamental rights. This study employs a normative legal research method using statutory, conceptual, and critical juridical approaches. The analysis focuses on disaster law norms, principles of administrative law, and the doctrine of constitutional state responsibility, particularly the concept of state omission. The findings demonstrate that disaster emergency indicators are objective, cumulative, and impact-based, and therefore cannot be reduced to administrative discretion or claims of state capacity alone. Empirically, the scale of casualties, damage to vital infrastructure, and cross-provincial reach indicate that the emergency threshold had been met, thereby narrowing policy discretion into a conditional legal obligation. Delaying the declaration of emergency status risks undermining command legitimacy, recovery budgeting, and the protection of the rights to life, health, and public safety. This article concludes that the Sumatra flood crisis risks transforming from a natural disaster into a constitutional disaster due to the absence of a decisive, transparent, and accountable legal determination by the state.